2009
DOI: 10.1080/02770900902849897
|View full text |Cite
|
Sign up to set email alerts
|

Allergic and Nonallergic Rhinitis: Can We Find the Differences/Similarities between the Two Pictures?

Abstract: The diagnostic challenge of rhinitis is to determine the etiology, specifically whether it is allergic or nonallergic. We therefore evaluated the general features of patients with allergic (AR) and nonallergic rhinitis (NAR), as well as health-related quality of life (HRQoL). The study group consisted of 323 patients (201 F/122 M) with a mean age of 31.79 +/- 12.64 years. Almost two thirds of the population had AR (63.5%). Neither the demographic characteristics nor the duration of rhinitis was different betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
30
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 20 publications
6
30
0
Order By: Relevance
“…Even though itching, sneezing and nasal obstruction were reported to be more common in atopic patients, rhinorrhea and nasal obstruction were found to be frequent symptoms of NAR, aside from the major symptoms of neurogenic activation found in other studies [3,5,21,22]. Other than symptoms, we used NIPF as an objective tool of nasal airflow and found that it was compatible with the symptom of nasal obstruction, as reported before [23].…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Even though itching, sneezing and nasal obstruction were reported to be more common in atopic patients, rhinorrhea and nasal obstruction were found to be frequent symptoms of NAR, aside from the major symptoms of neurogenic activation found in other studies [3,5,21,22]. Other than symptoms, we used NIPF as an objective tool of nasal airflow and found that it was compatible with the symptom of nasal obstruction, as reported before [23].…”
Section: Discussionmentioning
confidence: 56%
“…As mentioned in the World Allergy Organization guideline, the diagnosis of NAR implies exclusion of rhinosinusitis, mechanical/anatomical abnormalities as well as of concomitant diseases as causes of rhinitis symptoms [2]. Even though NAR is at least as common as allergic rhinitis (AR) [3,4], its mechanism is not clear, and it has been suggested to be a local allergic or a neurogenic response.…”
Section: Introductionmentioning
confidence: 99%
“…18 As was shown in our recent study, NAR was around one-fifth of the population with chronic rhinitis. 19 In our present study, higher asthma comorbidity in NAR patients may have been responsible for the insignificant difference compared with AR, using a validated marker of asthma-related inflammation, FeNO. Previous studies showed that those with rhinitis and asthma had significantly higher FeNO values compared with those without asthma.…”
Section: Discussionmentioning
confidence: 85%
“…This suggests that most of the complaints of rhinitis can be associated with non-allergic causes. While two-thirds of rhinitis cases are actually allergic [8,9,22], about one-fifth of rhinitis cases are allergic in Erzurum, which might be because Erzurum is one of the coldest and highest-altitude cities in Turkey. The lower rate of allergic rhinitis can be explained by the decreased amount of house dust mites and pollen in high altitudes, in addition to the frequent occurrence of respiratory tract infections in cold weather.…”
Section: Discussionmentioning
confidence: 99%